Clinical usefulness of serum antibodies as biomarkers of gastrointestinal and liver diseases. Issue 9 (September 2017) - Di Sabatino, Antonio; Biagi, Federico; Lenzi, Marco; Frulloni, Luca; Lenti, Marco Vincenzo; Giuffrida, Paolo; Corazza, Gino Roberto
Abstract: The progressively growing knowledge of the pathophysiology of a number of immune-mediated gastrointestinal and liver disorders, including autoimmune atrophic gastritis, coeliac disease, autoimmune enteropathy, inflammatory bowel disease, autoimmune hepatitis, primary sclerosing cholangitis, primary biliary cholangitis and autoimmune pancreatitis, together with the improvement of their detection methods have increased the diagnostic power of serum antibodies. In some cases – coeliac disease and autoimmune atrophic gastritis – they have radically changed gastroenterologists' diagnostic ability, while in others – autoimmune hepatitis, inflammatory bowel disease and autoimmune pancreatitis – their diagnostic performance is still inadequate. Of note, serum antibody misuse in clinical practice has raised a number of controversies, which may generate confusion in the diagnostic management of the aforementioned disorders. In this review, we critically re-evaluate the usefulness of serum antibodies as biomarkers of immune-mediated gastrointestinal and liver disorders, and discuss their pitfalls and merits.